2017
DOI: 10.3835/plantgenome2017.02.0010
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Screening for Lectin Motifs in Arabidopsis thaliana

Abstract: For more than three decades, served as a model for plant biology research. At present only a few protein families have been studied in detail in . This study focused on all sequences with lectin motifs in the genome of . Based on amino acid sequence similarity (BLASTp searches), 217 putative lectin genes were retrieved belonging to 9 out of 12 different lectin families. The domain organization and genomic distribution for each lectin family were analyzed. Domain architecture analysis revealed that most of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 121 publications
3
54
0
Order By: Relevance
“…AtPAP26‐S2 isolated from the CCF of the −Pi cells appeared to be purified to electrophoretic homogeneity following lectin affinity chromatography on Con‐A Sepharose (Figure a). However, peptide mass fingerprinting by MALDI‐TOF MS of the excised 55‐kDa protein‐staining and anti‐AtPAP26 immunoreactive polypeptide obtained following Con‐A chromatography (Figure a) indicated that it was a mixture of AtPAP26 (At5g34850) and a member of Arabidopsis ' GNA (mannose‐binding) lectin family (Eggermont et al, ) encoded by gene loci At1g78850. Phenyl Superose FPLC of the pooled Con‐A fractions resolved a pair of protein peaks that both migrated as 55‐kDa polypeptides following SDS‐PAGE of the respective pooled fractions (Figure b,c); they were identified as At1g78850 and AtPAP26 following MALDI‐TOF MS analysis (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…AtPAP26‐S2 isolated from the CCF of the −Pi cells appeared to be purified to electrophoretic homogeneity following lectin affinity chromatography on Con‐A Sepharose (Figure a). However, peptide mass fingerprinting by MALDI‐TOF MS of the excised 55‐kDa protein‐staining and anti‐AtPAP26 immunoreactive polypeptide obtained following Con‐A chromatography (Figure a) indicated that it was a mixture of AtPAP26 (At5g34850) and a member of Arabidopsis ' GNA (mannose‐binding) lectin family (Eggermont et al, ) encoded by gene loci At1g78850. Phenyl Superose FPLC of the pooled Con‐A fractions resolved a pair of protein peaks that both migrated as 55‐kDa polypeptides following SDS‐PAGE of the respective pooled fractions (Figure b,c); they were identified as At1g78850 and AtPAP26 following MALDI‐TOF MS analysis (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Phenyl Superose FPLC of the pooled Con‐A fractions resolved a pair of protein peaks that both migrated as 55‐kDa polypeptides following SDS‐PAGE of the respective pooled fractions (Figure b,c); they were identified as At1g78850 and AtPAP26 following MALDI‐TOF MS analysis (Table S4). We have designated At1g78850 as AtGAL1 (i.e., G NA A pple L ectin‐ 1 ) because it belongs to the GNA domain lectin family (Eggermont et al, ) and has been annotated as a “D‐mannose binding lectin with an apple‐like carbohydrate‐binding domain” (www.araport.org/search/thalemine/at1g78850).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations